Pendekatan pencegahan kaunselor Muslim dalam menangani salah laku pelajar sekolah menengah di daerah Klang, Selangor - Halimah Abd Halim,; Zainab Ismail, (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2015)
Muslim counselor in school is a professional guide who can help schools to reduce students’ misbehavior and to implement Islamic values as a way of life. The Islamic approach is the approach implemented by the school counselor in dealing student’s misbehavior. However, the practice of Islamic approach using by Muslim counselor at school in dealing with students’ misbehavior has not been studied extensively. This paper is aimed to discuss and analyze the Islamic approach adopted by the Muslim counselor as an effort to deal the students’ misbehavior in secondary schools in Klang District, Selangor. Data in this paper were collected through a quantitative survey research. By using purposive sampling, a total of 73 Muslim counselors from secondary schools in the Klang District were selected as respondents. Data were analyzed using descriptive statistical techniques. The study shows that Muslim counselor in schools has implemented the Islamic preventive approach through programs such as anti-smoking talks, HIV and AIDS talks, self-identity courses, leadership courses, religious talks, and visiting program to rehabilitation center. This study also shows that Muslim counselor practicing Islamic preventive approach in dealing students’ misbehavior such as guiding students to perform solat fardu five times a day, to respect human being and environment, to behave with persistence, to commit with a good or ma`ruf deed, and to select a good mass media. As a whole, the Islamic preventive approach by the Muslim counselor has given a huge implication especially to develop an Islamic counseling index in dealing students’ misbehavior.